2023
DOI: 10.1007/s11423-023-10227-y
|View full text |Cite
|
Sign up to set email alerts
|

Learning critical thinking skills online: can precision teaching help?

Abstract: Critical thinking is identified as a key educational outcome in higher education curricula; however, it is not trivial to support students in building this multifaceted skill. In this study, we evaluated a brief online learning intervention focusing on informal fallacy identification, a hallmark critical-thinking skill. The intervention used a bite-sized video learning approach, which has been shown to promote student engagement. Video-based learning was implemented within a precision teaching (PT) framework, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…The results of this study showed that the use of ChopMelon Net significantly improved users' critical thinking and problem-solving skills, which is consistent with previous research that suggests that integrating real-world problems into instruction is an effective way to improve these skills [52,53]. The complexity and dynamics of real-world problems require learners to use and integrate knowledge from different domains while encouraging them to adopt an active learning attitude [54].…”
Section: Discussionsupporting
confidence: 87%
“…The results of this study showed that the use of ChopMelon Net significantly improved users' critical thinking and problem-solving skills, which is consistent with previous research that suggests that integrating real-world problems into instruction is an effective way to improve these skills [52,53]. The complexity and dynamics of real-world problems require learners to use and integrate knowledge from different domains while encouraging them to adopt an active learning attitude [54].…”
Section: Discussionsupporting
confidence: 87%
“…Presenting students with multiple AI-generated answers to a problem or question and asking them to evaluate the correctness and reasoning behind each solution encourages active engagement with the content and the development of their analytical skills. Another way to facilitate understanding of the problem-solving process is to encourage students to follow the logic employed by AI in reaching a given solution (example in Supporting Information, Section C). , This will help them understand the steps involved and recognize the importance of structured thinking in problem-solving. For example, in a chemistry problem involving stoichiometry, an AI-generated solution might involve identifying the limiting reactant, applying relevant stoichiometric coefficients, and using the given data to calculate the amount of a product formed.…”
Section: Main Concerns and Potential Solutionsmentioning
confidence: 99%
“…However, the influx of information necessitated stronger information and data literacy skills. Today, AI-powered systems are altering how we acquire and process information. These tools might reduce the need to memorize basic facts or perform simple reasoning tasks but cannot replace the necessity for high-level educational goals such as analysis, evaluation, or synthesis of new material. , The capacity to synthesize, connect, and apply scientific concepts in novel ways remains paramount. In response to whether instructors should continue to assess students based on writing clarity and formatting, we posit that it is not necessary to grade students solely on their writing skills, particularly when advanced AI tools can accomplish these tasks.…”
Section: Main Concerns and Potential Solutionsmentioning
confidence: 99%
See 2 more Smart Citations